Energy code effectiveness on GHG emission mitigation for single-family houses in Canada. (25th May 2021) - Li, Bo; Rowe, Andrew; Wild, Peter
Abstract: The building sector is a significant source of GHG emissions and has great potential for emission reductions. The effectiveness of building energy codes on energy savings and emission mitigation is of a primary concern to policy makers, but uncertainty in cost and benefit in different regions complicates code selection and implementation. The impacts of a specific building energy standard vary depending on the heating system's thermal efficiency and the heating fuel's carbon intensity. This paper examines the GHG emissions due to space heating for new construction single-detached households in Canada under different building energy codes and enforcement scenarios. The two codes considered are the BC step code and Passive House criteria. Three scenarios are examined reflecting different levels of stringency of standards between 2020 and 2032. The results show both BC step code and passive house criteria can help mitigate the space heating GHG emissions. There is no significant difference between the BC step code and the passive house criteria from the perspective of GHG emission reduction in the province of British Columbia; however, when implemented nationwide, the passive house criteria is 12% more effective in abating space heating GHG emissions than the most stringent level (i.e. Step 5) of BC step code. Highlights: Passive House criteria are more effective in reducing the space heating GHG emissions than BC Step Code does in Canada. BC Step Code and Passive House criteria can save space heating GHG emissions of new single-houses by 77% and 89%, respectively. Building performance standards are less impactful in regions where fuel carbon intensity is low. No notable difference is found between BC Step Code and Passive House criteria in GHG emission reduction per unit area in BC.